Determination of river water composition trends with uncertainty: Seasonal variation of nutrients concentration in Tagus river estuary in the dry 2017 year. (September 2020) - Borges, Carlos; Bettencourt da Silva, Ricardo J.N.; Palma, Carla
Abstract: The assessment of long-term trends in river water composition is hampered by river composition heterogeneity, and sampling and sample analysis uncertainty. This work describes a novel methodology for the reliable detection of small river composition trends by taking all relevant uncertainty components into account. The methodology was applied to study the variation of nutrients concentration of Tagus river estuary in the extremely dry 2017 year. Mean nutrient concentrations were determined with an uncertainty that combines sampling and sample analysis uncertainty by the Monte Carlo Method. The nutrient concentration variation observed in two occasions is meaningful if the difference of mean concentrations is metrologically different from zero for a 95% confidence level. The observed meaningful NO2 increase, and SiO2 and NOx variations is justified by dissolved oxygen reduction, decreased freshwater input and algal productivity variations. The developed tool can be applied to the assessment of other composition trends in rivers. Graphical abstract: Unlabelled Image Highlights: Methodology for distinguishing small composition trends of a large river area Concentration variations determined with sampling and sample analysis uncertainty Variation of nutrients concentrations in Tagus river estuary in the very dry 2017 NO2, SiO2 and NOx variations justified by physicochemical and biological processes